2001
DOI: 10.1093/rheumatology/40.3.336
|View full text |Cite
|
Sign up to set email alerts
|

The role of hyaluronic acid in protecting surface‐active phospholipids from lysis by exogenous phospholipase A2

Abstract: It is reasonable to assume that HA plays an important indirect role in the steady state of the boundary lubrication process of joints by protecting SAPL from being lysed by PLA(2). However, as excessive loading generates free radicals within the joint (among other effects), the HA that is degraded in this way is incapable of protecting SAPL from lysis by PLA(2). When the rate of degradation exceeds that of synthesis, there will be insufficient replacement of HA and/or SAPL, resulting in denudation of the artic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
62
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(66 citation statements)
references
References 30 publications
4
62
0
Order By: Relevance
“…If phospholipase was incubated for 30 min with hyaluronan before its addition to the specimen, µ increased to an extent similar to that occurring with phospholipase not preincubated with hyaluronan. Therefore, the effect of hyaluronan described was not due to an inhibition of the enzyme caused by hyaluronan, but is a protection of the pleural phospholipids from the action of phospholipase, similar to that described for alveolar surface active phospholipids [53,55], and for synovial phospholipids [54]. Moreover, the small increase in µ observed after a short treatment with phospholipase in the presence of hyaluronan pre-treatment was removed by the addition of hyaluronan, similarly to what occurred for the increases induced by blotting [26], short pronase treatment [34], and short phospholipase treatment [38].…”
Section: Phospolipids Lubricant Effectssupporting
confidence: 63%
See 1 more Smart Citation
“…If phospholipase was incubated for 30 min with hyaluronan before its addition to the specimen, µ increased to an extent similar to that occurring with phospholipase not preincubated with hyaluronan. Therefore, the effect of hyaluronan described was not due to an inhibition of the enzyme caused by hyaluronan, but is a protection of the pleural phospholipids from the action of phospholipase, similar to that described for alveolar surface active phospholipids [53,55], and for synovial phospholipids [54]. Moreover, the small increase in µ observed after a short treatment with phospholipase in the presence of hyaluronan pre-treatment was removed by the addition of hyaluronan, similarly to what occurred for the increases induced by blotting [26], short pronase treatment [34], and short phospholipase treatment [38].…”
Section: Phospolipids Lubricant Effectssupporting
confidence: 63%
“…Therefore, in both series of experiments, the behavior of the two macromolecules was similar to that occurring in post-blotting Ringer [26], and after short pronase treatment [34]. The increase in µ after short phospholipase treatment provided the opportunity to check whether hyaluronan protects the phospholipids of the pleural mesothelium surface from the action of phospholipase, in analogy to the following findings obtained in other tissues: (a) hyaluronan [53] decreases alveolar surfactant inactivation by serum; (b) hyaluronan decreases the lysis of synovial phospholipids produced by phospholipase [54]; and (c) hyaluronan decreases alveolar surfactant inhibition caused by phospholipase [55]. Actually, if hyaluronan (2.5 mg/mL) was placed on the specimen before the short treatment with phospholipase, the increase in µ produced by this enzyme was smaller than that occurring without previous addition of hyaluronan.…”
Section: Phospolipids Lubricant Effectssupporting
confidence: 52%
“…Possibly the quaternary amino group of DPPC is attracted to the carboxyl group of HA to form a salt linkage. Another in vitro study by Nitzan et al [41] indicated that HA adhered to the phospholipid membrane (liposomes) fi rmly, thus forming a barrier against lysis by phospholipase A 2 . Zasadzinski et al [42] have suggested a general mechanism whereby polymers like HA increase rates of surfactant adsorption to air-liquid interfaces by enhancing 'depletion forces', that tend to aggregate surfactant microstructures.…”
Section: Discussionmentioning
confidence: 99%
“…18 In OA joint diseases, the concentration and molecular weight of HA decrease 16,19 and the synovial fluid becomes more abundant, less viscous and reduced in elastoviscous properties that may culminate in a painful condition for the patient. Viscosupplementation 20,21 was identified as an effective treatment of OA with a small number of adverse effects.…”
Section: Introductionmentioning
confidence: 99%